Causal effects of closing businesses in a pandemic - Barrot, Jean-Noël; Bonelli, Maxime; Grassi, Basile; Sauvagnat, Julien (Journal of Financial Economics, 2024)
We study whether state-level mandatory business closures implemented in response to the outbreak of the Covid-19 causally affect economic and health outcomes. Using plausibly exogenous variations in exposure to these restrictions, we find that they impose substantial losses to firms and workers, the former bearing approximately two thirds of the cost, consistent with firms partially insuring their workers. We show that mandatory business closures have a significant negative causal effect on mortality rates, particularly in areas featuring contact-intensive occupations. We discuss the assumptions under which the health benefits of business closures exceed their associated economic costs.